SEGMENTASI PASAR PRODUK KUE KERING TRADISIONAL PADA HOME INDUSTRI CUCURU DI KABUPATEN BANTAENG - Halim, Hasriliandi (AgriMu, 2023)
The purpose of this study was to determine the market segmentation of traditional pastries at the Cucuru Home Industry. This research was conducted at the Cucuru Home Industry in Bissappu District, Bantaeng Regency. The location determination was carried out by purposive sampling with the consideration that the Cucuru Home Industry had been established since 2001 with a very large number of consumers. This research was conducted in February-April 2022. This study used a case study research technique with qualitative descriptive research methods. The basis that can be used in conducting market segmentation is the main variables used in market segmentation based on Kotler's thinking, namely Geographic, Demographic, Psychographic, and Behavioral. The results of this study indicate that traditional pastries made at the Cucuru Home Industry can be reached by many levels of society, including the location where the pastries are marketed and the prices offered to consumers. The choice of traditional pastry products at the Cucuru Home Industry is generally a special snack for those who have more daily activities outside the home. In addition, traditional pastries at the Cucuru Home Industry are being hunted by many consumers because they are mandatory food in every traditional event and wedding held in the area. So this situation greatly affects consumer interest in buying. In addition, many consumers of Home Industry Cucuru from Makassar City and surrounding communities who passed through Bantaeng Regency during the holidays and finally decided to choose this location as a place to buy souvenirs to bring to relatives at home. The income of the urban community, which tends to be high, also determines their consumption patterns, including their decision to buy traditional pastries from the Cucuru Home Industry. Even some of the consumers have become regular consumers since the last 20 years.